2019
DOI: 10.3390/cancers11121975
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Treatment Goes Viral: Using Viral Proteins to Induce Tumour-Specific Cell Death

Abstract: Cell death is a tightly regulated process which can be exploited in cancer treatment to drive the killing of the tumour. Several conventional cancer therapies including chemotherapeutic agents target pathways involved in cell death, yet they often fail due to the lack of selectivity they have for tumour cells over healthy cells. Over the past decade, research has demonstrated the existence of numerous proteins which have an intrinsic tumour-specific toxicity, several of which originate from viruses. These tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 183 publications
(238 reference statements)
0
11
0
Order By: Relevance
“…Therefore, the study on the CAV ORF3 protein provides a unique system for identifying apoptosis pathways ( Maddika et al., 2006 ) that can kill cancer cells selectively independent of p53. Currently, many studies on the CAV ORF3 protein aim to deliver the protein as a potentially safe cancer chemotherapy drug ( Ruiz-Martínez et al., 2017 ; Castro et al., 2018 ; Wyatt et al., 2019 ). Clearly, continued studies of pathways related to cell death have obvious therapeutic value ( Hough et al., 2015 ), although the induction activities of the PCV and DuCV ORF3 proteins are weaker than the activity of the CAV ORF3 protein.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the study on the CAV ORF3 protein provides a unique system for identifying apoptosis pathways ( Maddika et al., 2006 ) that can kill cancer cells selectively independent of p53. Currently, many studies on the CAV ORF3 protein aim to deliver the protein as a potentially safe cancer chemotherapy drug ( Ruiz-Martínez et al., 2017 ; Castro et al., 2018 ; Wyatt et al., 2019 ). Clearly, continued studies of pathways related to cell death have obvious therapeutic value ( Hough et al., 2015 ), although the induction activities of the PCV and DuCV ORF3 proteins are weaker than the activity of the CAV ORF3 protein.…”
Section: Discussionmentioning
confidence: 99%
“…The intracellular accumulation of NS1 protein owing to its bipartite nuclear localization sequence (NLS) between aa residues 194 and 216, is a major effector of the virus-induced cytotoxicity of the neoplastic cells. Furthermore, modification of specific residues (Thr-435 and Ser-473) of NS1 is important for cancer cell toxicity which is exerted, at least in part, by dysregulation of intracellular signaling pathways [ 13 ]. Cell death caused by NS1 was shown to be majorly induced by apoptosis and dependent on caspase-9-driven caspase-3 activation [ 14 ].…”
Section: Human Viral Proteins As Anticancer Agentsmentioning
confidence: 99%
“…Small CPPs, such as Tat, are used as ideal tools for the delivery of apoptin and AdP in vitro and in vivo. Other cationic fusion systems, namely human-derived CPP 10 (hpp10), protein transduction domain 4 (PTD4), VP1 from chicken anemia virus (CVP1) were also found to penetrate tumor tissues in vivo [ 13 , 61 ]. MT23, a CPP screened by phage display in B16 melanoma cells, was shown to not able to enter normal human cells but only melanoma cells, and MT23- fused apoptin significantly inhibited tumor growth and induced cell apoptosis in B16 tumor-bearing mice.…”
Section: Administration Toolsmentioning
confidence: 99%
“…As of now, the exact mechanisms by which viruses lead to tumor development are not fully understood. Several studies demonstrated that viral infection is not sufficient for cancer development by itself [11,12] but that they contribute to oncogenesis through oncogenic viral protein production, chronic inflammation, and deregulation of host cell homeostasis [2,[13][14][15][16]. Epigenetic alterations provide a common mechanism of virusinduced transformation.…”
Section: Introductionmentioning
confidence: 99%